Assembly Sequence Planning Based on Hierarchical Model. (9th February 2022) - Li, Chunxi; Hou, Wenjun
Abstract : With the rapid development of intelligent manufacturing technology and ultraprecision machining, assembly technology has attracted more and more attention. Assembly sequence is an important part of assembly process planning. However, assembly sequence is affected by many complex factors, such as the time required to assemble products, the geometric feasibility of assembly sequence, and other factors (tool replacement times and assembly direction change), so it is very challenging. In this paper, an assembly information model based on geometric features of parts is proposed. The model obtains the hierarchical information of the part through the segmentation and feature reconstruction of the part. Based on the influence of the contact surface between parts on the feasible motion domain and assembly domain, the assembly constraint relationship model is established. The objective function is constructed by changing the assembly direction, changing the assembly tools, and evaluating the assembly fit type. The geometrically feasible assembly sequence is optimized to obtain the optimal assembly sequence under the existing conditions. Taking a block, a secondary reducer spindle, and a cylinder as examples, the effectiveness of the method is verified.